Diagnóstico médico por meio de relações Fuzzy: Dengue, Chikungunya ou Zika - Marins, Lazaro Rodrigo de (2016)
This research aims to use the fuzzy relations to diagnose patients infected with the virus transmitted by the mosquito Aedes aegypti, which can be diagnosed with dengue, chikungunya or zika. For this we use fuzzy relational equations to propose a model of medical diagnosis. The basic idea is to relate the symptoms or signs of patients with these three diseases. First we studied basic concepts of Fuzzy Sets Theory through definitions, theorems and examples.